An Ethnographic Study of Consumption, Saving, and Investment Patterns of Minang Millennial Parents in Jakarta with Islamic Wealth Management Perspective - Andi Shabrina; khaerud Dawam; Muhammad Farhan; Jerry Heikal (Prodi Ekonomi Syariah, Fakultas Syariah, Institut PTIQ Jakarta, 2022)
The purpose of this study is to see how the opinion of the Minang ethnic group of parents in Jakarta regarding Islamic wealth management related to consumption, saving and investment patterns. The Minang ethnic community, which has a philosophy of traditional life, adat basandi syara-syara basandi kitabullah (Yoserizal, 2018) means that customs are side by side with sharia. sharia is side by side with the book of Allah (al-Quran) and is also known as an ethnic group that is hardworking, good at trading, likes to migrate, and also closely holds religious values. Assets in the view of Islam are a mandate and must be maintained and managed as well as possible for the benefit of themselves, their families, and others through zakat, infaq, shodaqo, and waqf. The millennial generation lives in an era of rapid information flow, in several studies shows that the largest income earned is used for consumptive activities, compared to storage and investment options. This research is a type of qualitative research using an ethnographic study approach. There are 8 respondents, they are Minang ethnic who was born in the millennial era, already have children, and live in Jakarta. The results show that the pattern of financial regulation of the ethnic Minang millennium has philosophical values of Minang customs which are adat basandi syara-syara basandi kitabullah, this is in line with the pattern of Islamic Wealth Finance, such as obtaining halal assets and goods for getting blessings in personal and household life. Regarding the allocation of Ziswaf (zakat, infaq, alms and waqf) in an effort to purify property, some respondents have budgeted regularly and some do it spontaneously. This is in accordance with the Minang saying, anak ikan dimakan ikan, gadang ditabek anak tenggiri. Ameh bukan perakpun bukan, budi saketek rang haragoi which means that we are on good terms not because of wealth but because of kindness. Respondents also believe that in regulating consumption patterns, parents must set a priority scale. The goal is to manage family finances so that it goes according to what the family expects. This is in line with the Minang saying,katiko ado ditahan Lah tak ado baru dimakan which means that if there is a saying that violates wasting, it should be stored and removed if necessary.